An overview on the cult of sweet chestnut and presentation of the greatest Hungarian sweet chestnut trees - Takács, Márton; Malatinszky, Ákos (JOURNAL OF LANDSCAPE ECOLOGY, 2012)
An overview of the European and the Hungarian sweet chestnut cult is given as several legends and folk feasts are connected to this species, similarly to other ones such as linden, willow or oak. Authors have investigated on measures of sweet chestnut trees with the greatest perimeter in Hungary, which, despite their giant sizes, or because of high age, are seriously threatened. Based on our dendrometrical measurements, the greatest sweet chestnut tree lives near Nagykutas village (SW-Hungary), among wine cellars. Patchy remnants of one-time extended chestnut groves near Zengővárkony or Velem have also preserved some giants as well as wine yards around Surd. The greatest chestnut tree of Vas County (W-Hungary) thrives near Torony village, among tall shrubs. The greatest ones in Somogy County (SW-Hungary) live around Iharosberény. Besides them, measurement data are presented from Zalaegerszeg, Dióskál, Bak, Csepreg and Csipkerek.